A compact quasi 3D threshold voltage modeling and performance analysis of a novel linearly graded binary metal alloy quadruple gate MOSFET for subdued short channel effects. (June 2015) - Sarkhel, Saheli; Sarkar, Subir Kumar
Highlights: Potential minima of the WFEG QG MOS is higher than that of the normal QG equivalent. The proposed WFEG QG MOS structure exhibits superior DIBL performance as compared to its normal QG counterpart. WFEG QG structure exhibits higher SCE immunity by virtue of having a lower value of threshold voltage roll off. A thin gate oxide results in a smaller value of natural length which induces lower value of threshold voltage roll-off. With gradual decrease of channel thickness, the threshold voltage of the quantum case shows a sharp deviation from that of the classical case. Abstract: In the present era of low power devices, to keep pace with the aggressive scaling demands, the concept of surrounding gate MOS geometry is gradually being popular among the researchers for enhancing the performance of nanoscale MOSFETs due to the inherent benefit of the gate-all-around geometry compared to the conventional planar structures. In this research endeavour, we have, for the first time, incorporated the novel theory of work function engineering of a binary metal alloy gate with continuous horizontal variation of mole fraction in a fully depleted quadruple gate MOSFET, thereby proposing a new structure namely Work Function Engineered Gate Quadruple Gate MOSFET (WFEG QG MOSFET). A detailed analytical modeling of this novel WFEG QG MOS structure has been formulated to present a quasi 3D threshold voltage model based on 3D scaling equation instead of the tedious solution of 3D Poisson's equation. The device short channel effects have been included by calculating the natural length of the proposed QG device using the effective number of gate (ENG) concept. An overall comparative performance analysis of the WFEG QG MOS and normal QG MOSFET has been done to establish the superiority of the proposed WFEG structure over its QG equivalent in terms of reduced Short Channel Effects (SCEs), Drain Induced Barrier Lowering (DIBL) and Threshold Voltage Roll Off (TVRO). The results of our analytical modeling are found to be in good agreement with the simulation results, thereby establishing the accuracy of our modeling.